2022
DOI: 10.3389/fpls.2022.962664
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco shred varieties classification using Multi-Scale-X-ResNet network and machine vision

Abstract: The primary task in calculating the tobacco shred blending ratio is identifying the four tobacco shred types: expanded tobacco silk, cut stem, tobacco silk, and reconstituted tobacco shred. The classification precision directly affects the subsequent determination of tobacco shred components. However, the tobacco shred types, especially expanded tobacco silk and tobacco silk, have no apparent differences in macro-scale characteristics. The tobacco shreds have small size and irregular shape characteristics, cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…An image acquisition darkroom with four photographic reflectors was designed to obtain high-quality tobacco shred images. Figure 3 is a photograph of an image acquisition system ( Niu et al., 2022 ). The camera and light source were fixed on the bracket, including the universal light source lighting frame, the settings of which could be changed with a fine-tuning knob attached to a 600 mm threaded rod.…”
Section: Data Acquisition and Preprocessingmentioning
confidence: 99%
See 2 more Smart Citations
“…An image acquisition darkroom with four photographic reflectors was designed to obtain high-quality tobacco shred images. Figure 3 is a photograph of an image acquisition system ( Niu et al., 2022 ). The camera and light source were fixed on the bracket, including the universal light source lighting frame, the settings of which could be changed with a fine-tuning knob attached to a 600 mm threaded rod.…”
Section: Data Acquisition and Preprocessingmentioning
confidence: 99%
“…They found that both the accuracy and recall rate of the trained model were higher than 96%. Niu et al (2022) used ResNet50 as the network's primary framework and optimized it by increasing the multi-scale structure, in turn optimizing the number of blocks and loss function. Their experimental results showed that the network's tobacco shred classification accuracy was 96.56%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The implementation guidelines set out in Articles 9 and 10 of the WHO Framework Convention on Tobacco Control (FCTC) require manufacturers and importers of tobacco products to disclose the contents of tobacco products to government authorities, including the type of tobacco shred and blending ratio of each type of tobacco shred. Tobacco manufacturers must also have equipment and methods for detecting and measuring tobacco shred components [1,2]. According to the National Bureau of Statistics, China's cumulative cigarette production for the year 2021 reached 2418.24 billion, a cumulative increase of 1.3%.…”
Section: Introductionmentioning
confidence: 99%
“…Machine vision and deep learning methods have been studied in depth in the field of tobacco component detection. Niu et al [2] constructed a single tobacco shred dataset with four types by shooting single tobacco shreds and adopting a threshold preprocessing algorithm. The Resnet model was improved by changing the block parameters, multiscale fusion, and focal loss function.…”
Section: Introductionmentioning
confidence: 99%